DIFFERING APPROACHES OF THE JAPANESE GOVERNMENT TOWARDS THE “HISTORY ISSUES” - A. A. Batakova (Vestnik MGIMO-Universiteta)
The beginning of the 1990s saw a prevailing understanding in Tokyo that restoration of trust and reconciliation with East Asian countries should be the first step to a larger role of Japan in the international politics. This understanding manifested itself in so far the most successful attempts to apologize for the policies of Japan in the first half of the XX century, including Prime Minister T.Murayama's statement, issued in 1995, as well as measures to address the so-called"historical issues". By contrast, incumbent Prime Minister S.Abe, who is also striving to increase the role of Japan in the international arena, shows a gradual departure from the above-mentioned strategy on presumption that a "masochistic" view of Japanese history runs counter to its national interests. His statement on the occasion of the 70th anniversary of the end of World War II promoted a thesis on importance to lift "the burden of apologies". Given the fact that it was nevertheless received positively by Tokyo's main ally Washington and did not become an obstacle to political dialogue with Seoul and Beijing, the author suggests that S.Abe will continue step-by-step efforts to remove "historical issues" from the bilateral political and economic agenda with China and South Korea, as well as to erase the link between the necessity to issue apologies, characteristic of the Japanese diplomacy of the 1990s, and a strategy to a larger Japan's role in international politics and security.